Evaluation of the Potential for Soil Organic Carbon Content Monitoring With Farmers - Deluz, Cédric; Nussbaum, Madlene; Sauzet, Ophélie; Gondret, Karine; Boivin, Pascal (Frontiers in Environmental Science, 2020)
Increasing soil organic carbon (SOC) content is crucial for soil quality and climate change mitigation. SOC monitoring is indispensable to the corresponding policies and should provide results at farm scale to allow for incentives. In Switzerland farmers perform mandatory analyses of the SOC content of the 0-20 cm topsoil of every field, based on a composite sample, at least every ten years. The corresponding results are stored in a database in canton of Geneva. These data may be relevant for topsoil SOC monitoring, in particular for carbon sequestration policies, provided that they show appropriate quality, which is analyzed in this study. The minimum detectable change (MDC) of past results calculated based on the observed SOC changes was 0.013 % g g-1 at canton scale (2700 fields). Based on extended sampling of three representative fields different sampling strategies were simulated to determine the best future sampling guidelines for farmers. Collecting 20 aliquots with a gouge on the field diagonals was considered the best sampling compromise with field MDC of about 0.1 % g g-1 and a sampling duration of 20 mn. Compared to this procedure, former farmers’ sampling was not biased in average but showed a variance of 0.22% g g-1 due to smaller number of aliquots and varying sampling depths. Based on the best sampling results and assumptions on farm-scale SOC variance or SOC differences, the MDCs at farm scale ranged from 0.21 to 0.12 % g g-1 (5 fields) and 0.09 to 0.05 % g g-1 (30 fields), respectively. These MDCs are small compared to published monitoring networks MDCs, and allow determining SOC change rates at farm scale, thus offering perspectives for inexpensive and efficient monitoring in the frame of soil quality or climate mitigation incentives. For the latter, however, additional information with equivalent soil mass and deeper layers carbon content would be necessary.